Digital Philosophy and Digital Theophany: LLMs as Ontological and Epistemological Mediums of Revelation in the Age of AI - Ja’far, Suhermanto (Journal for the study of religions and ideologies, 2026)
This article explores the metaphysical and epistemological possibilities of Large Language Models (LLMs) as a new medium of revelation in the age of artificial intelligence, drawing on the framework of digital philosophy. It examines how algorithmic technologies, particularly LLMs, have reshaped the way religious knowledge is understood, produced, and accessed. By revisiting the concept of theophany (the manifestation of the divine), this study proposes a conceptual approach that juxtaposes the theological traditions of revelation with the generative linguistic capabilities of AI. In this context, LLMs are not merely considered linguistic tools or technical media but are interrogated as potential representations or mediations of revelation within the contemporary digital environment. This study investigates the intersection of the ontology of revelation, algorithmic epistemology, and the emergence of new forms of digital spirituality arising from human interaction with AI systems. Employing an interdisciplinary methodology that includes the philosophy of technology, digital ethics, systematic theology, and media theory, this study highlights both the transformative potential and the risks of "digital theophany", including the mystification of machines and the erosion of religious authority in digital ecosystems. This concludes that rethinking revelation in the age of AI is not only necessary but urgent if theology is to remain relevant in an ever-evolving digital landscape.